2018
DOI: 10.1177/2158244018771729
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Financing Public Higher Education in Tanzania and the Fate of Quality Education: The Experience of Selected Universities

Abstract: This article examines the sources of funding for public university education in Tanzania. The article also examines the trends in Other Charges and Capital Development funding for selected public universities in Tanzania taking a leap of years from 2010/2011 to 2015/2016 and their implications for quality issues in the provision of higher education. Results indicate that the sources of financing for public universities in Tanzania are unreliable and unsustainable. The findings further show that government appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…This funding modality is similar to other public universities in Tanzania: the government provides the majority of funds but universities have to make up the rest through various privatisation measures such as collecting tuition fees from students, research cooperation with businesses and reaching out to aid donors. Together this provides the necessary financial, educational, research and institutional resources for development (Mgaiwa, 2018). Despite operating with both public and private income, Mokono still experienced a funding shortage.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This funding modality is similar to other public universities in Tanzania: the government provides the majority of funds but universities have to make up the rest through various privatisation measures such as collecting tuition fees from students, research cooperation with businesses and reaching out to aid donors. Together this provides the necessary financial, educational, research and institutional resources for development (Mgaiwa, 2018). Despite operating with both public and private income, Mokono still experienced a funding shortage.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…If no effort is put in place, and with employers starting to consider post graduate degrees, this will attract more students, that in the next half a century, we will have no quality master and Doctor of Philosophy (Ph.D.) degrees. For instance, in a study that was conducted by the Inter-University Council of East Africa in 2014, it found that close to 50 percent of graduates were completely grey and lacked the skills and competencies to execute duties in their area of training (McCowan, 2018). This paper thus offers the following probable remedies:…”
Section: So What Is the Way Forward?mentioning
confidence: 95%
“…The training that is given in our universities by the lecturers needs to be given critical considerations for the wellbeing of our future professionals; as lecturers qualifications is not the only parameter to be looked at for universities to attain their goals (Ouma, 2016). For instance, during every semester, students are given assessment forms to give a score card of the lecturers and course at large, though the outcome is not strictly adhered to (McCowan, 2017). The overall process also lacks credibility, as students might be intimidated to give high scores to lecturers and courses, they feel they want to pass, reduce cases of missing marks or repeat of the course in another semester.…”
Section: Correlation Between University Curriculum and Employers' Requirementsmentioning
confidence: 99%
“…2 by low-income country (LIC) and lower-middle-income country (LMIC) curves. In SSA countries, funding of the HE subsector is a critical issue due to inadequate and unsustainable financing sources and mechanisms (Mgaiwa, 2018). Empirical evidence shows that the economic inability in most African countries has been the stumbling block to adequate funding for HE (Tilak, 2015).…”
Section: Financing Of Higher Educationmentioning
confidence: 99%